Cost engineering and pricing in autonomous manufacturing systems - Fazlollahtabar, Hamed; Saidi-Mehrabad, Mohammed (Emerald Publishing Limited, 2019)
This book provides extensive insights and analysis into pricing models for autonomous manufacturing. Taking a cost engineering approach, it shows how businesses facing technological change can provide visibility to pricing sensitivity and maximize price, and profit in every transaction. The book pulls together the many elements of cost engineering; cost estimation, cost control, business planning and management, profitability analysis, cost risk analysis and project management, planning, and scheduling, and considers the many different approaches and methods for estimating or assessing costs. It aims to help companies with decision making, cost management, and budgeting with respect to product development, and highlights the importance of cost estimation during the early stages of product development. A discussion of appropriate pricing models is also included to determine the most effective course for handling operational costs in autonomous manufacturing systems in order to create a more productive and profitable system.Cost Engineering and Pricing in Autonomous Manufacturing Systems will provide new insights for researchers and students, as well as industrial practitioners interested in applied models which can be employed and implemented in real cases.
Prelims -- Chapter 1: Introduction -- Chapter 2: Concepts of costing in automation -- Chapter 3: Concepts of pricing in automation -- Chapter 4: Cost parameters and costing models in autonomous manufacturing -- Chapter 5: Cost engineering in autonomous manufacturing -- Chapter 6: Cost and price in autonomous manufacturing -- Chapter 7: Pricing models in autonomous manufacturing -- Chapter 8: Price optimization in autonomous manufacturing -- References and further reading -- Index.
Includes bibliographical references and index.
Print version record
Keywords: Computer integrated manufacturing systems; Flexible manufacturing systems; Business & Economics -- Industries / Manufacturing; Manufacturing industries